Respuestas

2014-01-13T03:04:28+01:00
1/5+2/10+1/5+4/10= (2+2+2+4)/10=10/10=1
3/6+1/6+4/12= (6+2+4)/12=12/12=1
3/8+1/2+1/8= (3+4+1)/8=8/8=1
 4/10+1/2+? =1 de donde    ?=1-
4/10-1/2= (10-4-5)/10=1/10  quedando 4/10+1/2+1/10=1
2/8+1/4+ ?=1 de donde ?=1-2/8-1/4=(8-2-2)/8=4/8  quedando  
2/8+1/4+ 4/8=1
1/6+3/6+ ?=1 de donde ?=1-1/6-3/6=(6-1-3)/6=2/6  quedando 
1/6+3/6+ 2/6=1
2/8+ ?+8/16=1 de donde ?=1-2/8-8/16=(16-4-8)/16=4/16  quedando 
2/8+ 4/16+8/16=1
2/6+ ?+1/3=1
de donde ?=1-2/6-1/3=(6-2-2)/6=2/6  quedando  2/6+ 2/6+1/3=1

listo :)